(untitled) (Journal of Global Arts Studies, 2025)
Background: In recent years, Chinese costume dramas have played an increasingly important role in cultural dissemination in Japan and South Korea. A number of costume dramas have achieved notable success in both artistic creation and market performance, thereby establishing a certain audience base in these two countries. Objective: This study aims to provide practical and valuable references and guidance for the international communication strategies of Chinese costume dramas. Methods: Through data collection and statistical analysis, the study examines the production trends of Chinese costume dramas and their dissemination in Japan and South Korea. By analyzing various internet platforms, including social media commonly used by audiences in the two countries, the research investigates the specific coding, dissemination characteristics, and communication effects of Chinese costume dramas. Furthermore, theoretical analysis is applied to identify the causes behind these communication outcomes and to propose strategies for enhancing the creation and international dissemination of Chinese costume dramas. Results: The study obtains relevant comparative data and identifies several existing problems in the dissemination process. By integrating theoretical perspectives with empirical findings, the research rationally analyzes these issues and proposes corresponding solutions. Conclusion: At present, audiences in Japan and South Korea generally show a positive reception toward Chinese costume dramas. However, compared with other internationally influential productions and local works in these countries, there remains considerable room for improvement. This situation places higher demands on the production quality of Chinese costume dramas, the sophistication of symbolic and cultural coding, and the completeness of marketing and communication strategies.